Analysis of pragmatism in fables Ahmad Matar: Analysis of pragmatism in fables Ahmad Matar - دکتر رسول بلاوي (lark, 2020)
Pragmatism is a philosophical approach that pays attention to the facts.and gives the originality to the act.This school is based on action. The main objective should be practical utility .The fable is used by some of the poets to express their ideas about political and social views.Animals naturally play the main role in it. fable is a story whose purpose is to Criticize the chaotic conditions of  political and social indirectly in the community. Ahmad Matar lived in an atmosphere full of tyranny.It seems obvious that why most of his lyrics was stated with legend(fable).     This research is based on the research library which is Descriptive - Analytical method and tries to analyze the pragmatism of Ahmad Matar's fables so that we can make the instances more prominent.Prgmatysm components of the fables of the poet with the terms of the realism the critical approach to reform ,and playing the  role of clarification. so the author attempts to analyze a large part of the poet's unspoken things  which is considered a part of the message. The results show that the purpose of Matar's fables from the perspective of pragmatism was to notify the people , Decolonization and the fight against tyrants,and the poet criticized the political tyranny according to the fable and the Political space is explored from the angle of pragmatics.
Keywords: contemporary literature, Prgmatysm, fable, Ahmad Matar.